Decoy-state quantum key distribution with a leaky source. (20th June 2016) - Tamaki, Kiyoshi; Curty, Marcos; Lucamarini, Marco
Abstract: In recent years, there has been a great effort to prove the security of quantum key distribution (QKD) with a minimum number of assumptions. Besides its intrinsic theoretical interest, this would allow for larger tolerance against device imperfections in the actual implementations. However, even in this device-independent scenario, one assumption seems unavoidable, that is, the presence of a protected space devoid of any unwanted information leakage in which the legitimate parties can privately generate, process and store their classical data. In this paper we relax this unrealistic and hardly feasible assumption and introduce a general formalism to tackle the information leakage problem in most of existing QKD systems. More specifically, we prove the security of optical QKD systems using phase and intensity modulators in their transmitters, which leak the setting information in an arbitrary manner. We apply our security proof to cases of practical interest and show key rates similar to those obtained in a perfectly shielded environment. Our work constitutes a fundamental step forward in guaranteeing implementation security of quantum communication systems.